Performance analysis of meander-type inductor in silicon and flexible technology. (October 2016) - Pajkanovic, Aleksandar; Stojanovic, Goran M.; Djuric, Snezana M.
Abstract: In this paper meander-type inductors are designed and fabricated in silicon and flexible technology in order to investigate the performance of this topology and the possibilities of its utilization in RF applications. The CMOS inductor occupies the area of 0.104 mm 2, whereas the area of the inkjet printed one on flexible substrate is 1693.44 mm 2 . In the CMOS case, the inductance is 2.8 nH up to 7 GHz, Q -factor is 3.9 at 8.42 GHz and the resonant frequency is at 20.04 GHz. The measured and simulated (ADS Momentum) results differ by as low as 7%. The flexible technology inductor yields inductance of 720 nH up to 30 MHz, Q -factor of 2.1 at 50 MHz, while the resonant frequency is at 92 MHz. The design of both components is presented in detail and obtained results are thoroughly discussed in this paper, showing that the meander topology implemented in either of these cutting edge technologies enables wideband inductor operation.